Enhancing Primary School Teacher Professionalism Through a Mobile-Based Reflective Supervision System - Rugaiyah Rugaiyah; Desi Rahmawati; Neti Karnati; Cecep Kustandi; Kamaludin Kamaludin; Rahmah Novianti (Perspektif Ilmu Pendidikan, 2025)
This study explores the development and implementation of a mobile-based clinical supervision application designed to improve the professional competence of primary school teachers in Indonesia. In response to the increasing demands for reflective teaching and sustainable professional development in the digital era, this research applies a systematic research and development (R&D) approach using the Waterfall model to design, validate, and field-test a supervision tool integrated into mobile platforms. The study engaged 100 primary school teachers and 9 experts in education technology and instructional design. Results indicate high user acceptance, improved reflective practices, and enhanced supervision transparency. The findings support the potential of mobile-based tools to foster teacher growth, inform school management decisions, and transform traditional supervision into a more collaborative and developmental process.